Factors associated with the functional capacity of elderly individuals with hypertension and/or diabetes mellitus - Thaciane Alves Mota; Manuela Bastos Alves; Valdenir Almeida da Silva; Francieli Aparecida de Oliveira; Priscilla Mécia Conceição de Brito; Rudval Souza da Silva (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To identify the association of sociodemographic and clinical factors with the functional capacity of elderly individuals with hypertension and/or diabetes mellitus. Method: An outpatient, non-probabilistic cross-sectional study, performed in two Health Units in a city from the inland of Bahia, Brazil, with a population of 100 elderly individuals monitored through the HIPERDIA Program. Data was collected using a questionnaire covering socio-demographic data, the Katz index and the Mini Mental State Examination. Results: The analysis showed that 45% of the respondents had some degree of dependence. In the multivariate analysis it as observed that the elderly individuals aged 70 years old or more presented 1.9 times more chances to develop some degree of dependence in relation to those under 70 years old. Considered the same age group, it was shown that those with concomitant comorbidities (hypertension and diabetes) were 1.7 times more likely to develop some dependence compared to those who only had hypertension. Conclusion and implications for practice: It was possible to conclude that functional capacity as a multifactorial condition in this population was determined by age and by the presence of comorbidities (hypertension and diabetes). Identifying these disability-conditioning factors allows for a better planning of nursing care based on promoting a healthy, independent and autonomous aging process.